(untitled) (International Journal of Food and Nutritional Sciences, 2021)
One of the numerous causes wreaking havoc on the global ecosystem is plastic trash. Problems arise as a result of variables such as the difficulty of recycling plastic and its restricted usage. Plastic is a significant kind of solid waste with significant global environmental consequences. The purpose of this experiment is to see how using poly-ethylene terephthalate (PET) as a partial replacement for fine aggregate in concrete affects the results. This material’s impacts on the physical and mechanical characteristics of concrete were investigated. A set of six concrete mixes using poly-ethylene terephthalate (PET) as a partial replacement for fine aggregate were created, with substitution levels of 0%, 10%, 20%, and 30%. The purpose of this experiment was to see how fresh and cured concrete behaved in terms of Slump Cone, compressive strength. The testing findings revealed a decrease in unit weight, that fine aggregate substitution damaged the mechanical characteristics of concrete at different rates, and that plastic waste can be disposed of in specified ratios, proving that it may be successfully used in industrial applications.